Agro-tech in Malaysia: literature review and knowledge sharing from agro-technology using nations - Mastoi, Qurat-ul-ain; Abdullah, Istikoma; Ahmad Dahlan, Abdul Rahman (IJSER, 2014)
This paper demonstrates agriculture-technology in Malaysia and includes a literature review from some other countries. This study compares the Agro-technology transformation program in several countries: Taiwan, South Korea, Thailand, Israel and Malaysia. How are they improving their economy, though agriculture? The concept of advanced technologies in agronomic systems has been given a significant role in the improvement of agricultural creations e.g. sustainable agriculture, livestock production and Crop yield, in order to maintain food security. This paper illustrates what kind of enhancement needs to heighten the Malaysia economy through agronomy, sharing a knowledge of agricultural technology and exploring the reasons why the agriculture economy is back on the policy agenda of Malaysia.